Nocturnal Desaturation in the Stroke Unit Is Associated With Wake-Up Ischemic Stroke. Issue 7 (July 2016) - Kim, Tae Jung; Ko, Sang-Bae; Jeong, Han-Gil; Lee, Ji Sung; Kim, Chi Kyung; Kim, Yerim; Nam, Kiwoong; Mo, Heejung; Joon An, Sang; Choi, Huimahn Alex; Yoon, Byung-Woo
Abstract : Background and Purpose—: Wake-up stroke (WUS) represents a quarter of all ischemic strokes and may be a specific subgroup. Nocturnal desaturation secondary to sleep-disordered breathing is an independent risk factor for stroke, but the association between nocturnal desaturation and WUS remains unclear. We investigated the relationship between nocturnal desaturation using oxygen desaturation index and WUS in patients with acute stroke in the stroke unit. Methods—: A total of 298 patients admitted for acute ischemic stroke to the stroke unit between July 2013 and May 2015 were enrolled. The oxygen desaturation index was calculated using pulse oximetry data sampled every 1 minute during 9 hours on the first night (10:00 PM–7:00 AM) of the stroke unit admission, and nocturnal desaturation was defined as an oxygen desaturation index of 5 at least per hour. We compared the clinical characteristics and nocturnal desaturations between patients with and without WUS. Results—: Among all patients (age, 67.7±12.6 years; male, 54.4%), 26.5% patients had WUS. The proportion of nocturnal desaturation was significantly greater in patients admitted with WUS (29.1% versus 12.3%, P =0.001). The age, sex, risk factors except for hyperlipidemia, stroke severity, and stroke mechanisms were similar between the 2 groups. After adjustment for covariates, it was found that nocturnal desaturation was significantly more common in the WUS group (odds ratio, 3.25; 95% confidence interval, 1.63–6.46). Conclusions—: Nocturnal desaturation was more frequently observed in patients admitted with WUS during the first night in the stroke unit. This suggests that nocturnal desaturation is a possible modifiable risk factor for the occurrence of WUS.